The Influence of the PBL Model Using a Differentiated Approach to Substance and Its Changes Topics on Student Learning Outcomes - Margareta Putri Mohi; Tirtawaty Abdjul; Citron S. Payu; Muhammad Yusuf; Nova Elysia Ntobuo; Nurhayati Nurhayati (Jurnal Ilmiah Profesi Pendidikan, 2025)
This research aims to determine the effect of the Problem-Based Learning (PBL) model through a differentiated approach to substance and its changes topics on student learning outcomes at SMP Negeri 12 Gorontalo. This research is experimental research, with the research design being One Group Pretest-Posttest Design. The population of this research is class VII students of SMP Negeri 12 Gorontalo. The sample consists of 3 classes, namely experimental class, replication 1, and replication 2, with the total sampling technique. The instruments used in this research are learning style tests, teaching modules, LKPD, teaching materials, and written tests (pretest-posttest) to see student learning outcomes. Then, the data is analysed using descriptive and inferential statistics, including normality tests, hypothesis tests, and n-gain analysis. The average score for class VII students is greater than the achieving learning objectives, shown by the average score of the experimental class of 78.08, replication 1 at 78.53, and replication 2 at 77.73, compared to the achieving learning objectives of 70. Based on hypothesis testing criteria where t is calculated in the experimental class, it was 5.404 compared to a t-table of 2.056; replication 1 obtained a t-count of 6.006 with a t-table of 2.037; and replication 2 obtained a t-count of 5.199 with a t-table of 2.064. It can be concluded that hypothesis testing in the three classes is t-count greater than t-table. Through a differentiated approach, the PBL model affects student learning outcomes.